(untitled) (Research, Society and Development, 2020)
Predictive microbiology has been applied, through mathematical models, in order to predict the behavior of microorganisms when exposed to varied growth conditions. This science has gained prominence since it allows to predict growth rates and lag phase duration of contaminating pathogenic microorganisms in food. In this context, this work aimed to evaluate the effect of temperature (10 to 45°C), pH (5.0 to 9.0), sodium chloride concentration (0 to 8.5%) and concentration of tamarind peel and seeds extract in 80% ethanol (0 to 10%) in the in vitro growth of Bacillus subtilis, Pseudomonas aeruginosa, Staphylococcus aureus, Salmonella Enteritidis and Enterococcus faecalis. The parameters were evaluated according to fractional factorial design 24-1 plus 3 central points. The bacteria were incubated under the proposed conditions and the primary model of Baranyi and Roberts was adjusted to the experimental data (correlation coefficients between 0.72 and 1.00), being obtained growth rates and lag time. For most conditions tested, growth was inhibited for all bacteria, with rates ranging from -0.03 to -6.04 Log UFC/mL h. From statistical analysis, it was verified that the pH was the parameter that most influenced the inhibition of bacteria after. However, the extract of tamarind peel and seeds was the main component for the inhibition of S. Enteritidis. In this study, the in vitro growth of pathogenic bacteria in a culture medium containing tamarind peel or seeds extract was predicted. These extracts showed potential to be used in future applications as a natural antimicrobials.